Berteologi Bencana Di Tengah Pandemi Covid 19 - Alexander Stevanus (Sekolah Tinggi Agama Kristen Lentera Bangsa Manado, 2022)
Since 2019 or more or less the last 2 years the world and specifically in Indonesia have experienced a major outbreak, namely the COVID-19 pandemic or the corona virus outbreak. It is undeniable that this epidemic has greatly affected human life in all aspects and existing realities. Not only that, the great plague that has hitherto hit has also changed the face of the world and especially the church. The church became limited in its activities and even this disaster made people who felt the impact to question God in his justice. This study aims to be able to develop a theology that can be applied by the church in the midst of the covid 19 pandemic. This research was designed using a qualitative approach, where data sources were obtained through library documents. In this study, the effort of disaster theology formulates two things that can serve as guidelines for the church in dealing with the COVID-19 pandemic, namely: 1) church free day (the re-interpreting the meaning of worship and, 2) Understanding God's theodicy in human life